Boosting BCG with MVA85A: the first candidate subunit vaccine for tuberculosis in clinical trials. - Mcshane, H; Pathan, A; Sander, C; Goonetilleke, N; Fletcher, H; Hill, A (2005)
There is an urgent need for an improved vaccine against tuberculosis. Heterologous prime-boost immunization regimes induce higher levels of cellular immunity than homologous boosting with the same vaccine. Using BCG as the priming immunization in such a regime allows for the retention of the beneficial protective effects of BCG against disseminated disease in childhood. Recombinant poxviruses are powerful boosting agents, for both CD4+ and CD8+ T cells. Here we review the preclinical data from a BCG prime-recombinant modified vaccinia virus Ankara expressing antigen 85A (MVA85A) boost strategy. MVA85A is now in clinical trials in the UK and Africa and the design of these trials, including the ethical and regulatory issues are discussed.